MicroRNA miR-155 Activity in Mouse Choline Acetyltransferase-Positive Neurons Is Critical for the Rate of Early and Late Paraplegia After Transient Aortic Cross-Clamping - Kelani, Hesham; Nuovo, Gerard; Bratasz, Anna; Rajan, Jayanth; Efanov, Alexander A.; Michaille, Jean-Jacques; Awad, Hamdy; Tili, Esmerina (Frontiers in Molecular Neuroscience, 2022)
Aortic aneurism open repair surgery can cause spinal cord (SC) injury with 5-15 % of patients developing paraparesis or paraplegia. Using a mouse model of transient aortic cross-clamping (ACC), we have previously found that the expression of proinflammatory microRNA miR-155 increases in motoneurons (MNs) and endothelial cells (ECs) of ischemic SCs, and that global miR-155 deletion decreases the rate of paraplegia by 37.4% at 48-hours post-ACC. Here, we investigated the cell-specific contribution of miR-155 in Choline acetyltransferase-positive (ChAT+) neurons (that include all MNs of the SC) and ECs to SC injury after ACC. Mice lacking miR-155 in ChAT+ neurons (MN-miR-155-KO mice) developed 24.6% less paraplegia than control mice at 48-hours post-ACC. In contrast, mice lacking miR-155 in ECs (ECs-miR-155-KO mice) experienced the same rate of paraplegia as control mice, despite presenting smaller central cord edema. Unexpectedly, mice overexpressing miR-155 in ChAT+ neurons were less likely than control mice to develop early paraplegia during the first day post-ACC, however they reached the same rate of paraplegia at 48-hours. In addition, all mice overexpressing miR-155 in ECs (ECs-miR-155-KI mice) were paraplegic at 48-hours post-ACC. Altogether, our results suggest that miR-155 activity in ChAT+ neurons protects the SC against ischemic injury during the first day post-ACC before becoming deleterious during the second day, which indicates that early and late paraplegias arise from different molecular malfunctions. These results point to the need to develop specific protective therapeutics aimed at inhibiting both the early and late deleterious events after open repair surgery of aortic aneurisms.